Comparative Efficacy and Safety of Metformin, Glyburide, and Insulin in Treating Gestational Diabetes Mellitus: A Meta-Analysis. (4th November 2019) - Guo, Lanlan; Ma, Jing; Tang, Jia; Hu, Dingyao; Zhang, Wei; Zhao, Xue
Abstract : To compare the efficacy and safety of metformin, glyburide, and insulin in treating gestational diabetes mellitus (GDM), a meta-analysis of randomized controlled trials (RCTs) was conducted. PubMed, Embase, CINAHL, Web of Science, and Cochrane Library to November 13, 2018, were searched for RCT adjusted estimates of the efficacy and safety of metformin, glyburide, and insulin treatments in GDM patients. There were 41 studies involving 7703 GDM patients which were included in this meta-analysis; 12 primary outcomes and 24 secondary outcomes were detected and analyzed. Compared with metformin, insulin had a significant increase in the risk of preeclampsia (RR, 0.57; 95% CI, 0.45 to 0.72; P < 0.001 ), NICU admission (RR, 0.75; 95% CI, 0.64 to 0.87; P < 0.001 ), neonatal hypoglycemia (RR, 0.57; 95% CI, 0.49 to 0.66; P < 0.001 ), and macrosomia (RR, 0.68; 95% CI, 0.55 to 0.86; P < 0.05 ). To the outcomes of birth weight and gestational age at delivery, insulin had a significant increase when compared with metformin (MD, 114.48; 95% CI, 37.32 to 191.64; P < 0.01 ; MD, 0.23; 95% CI, 0.12 to 0.34; P < 0.001 ; respectively). Of the two groups between glyburide and metformin, metformin had lower gestational weight gain compared with glyburide (MD, 1.67; 95% CI, 0.26 to 3.07; P < 0.05 ). Glyburide had a higher risk of neonatal hypoglycemia compared with insulin (RR, 1.76; 95% CI, 1.32 to 2.36; P < 0.001 ). This meta-analysis found that metformin could be a safe and effective treatment for GDM. However, clinicians should pay attention on the long-term offspring outcomes of the relative data with GDM patients treated with metformin. Compared with insulin, glyburide had a higher increase of neonatal hypoglycemia. The use of glyburide in pregnancy for GDM women appears to be unclear.